2013
DOI: 10.1126/science.1238328
|View full text |Cite
|
Sign up to set email alerts
|

Fe-S Cluster Biosynthesis Controls Uptake of Aminoglycosides in a ROS-Less Death Pathway

Abstract: All bactericidal antibiotics were recently proposed to kill by inducing reactive oxygen species (ROS) production, causing destabilization of iron-sulfur (Fe-S) clusters and generating Fenton chemistry. We find that the ROS response is dispensable upon treatment with bactericidal antibiotics. Furthermore, we demonstrate that Fe-S clusters are required for killing only by aminoglycosides. In contrast to cells, using the major Fe-S cluster biosynthesis machinery, ISC, cells using the alternative machinery, SUF, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
225
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(242 citation statements)
references
References 42 publications
14
225
2
1
Order By: Relevance
“…Interesting recent work has illustrated that phenotypes such as cell death, mutagenesis, oxidative stress, and related activation of OxyR can all be reduced, depending on the method of culturing (101). These findings are consistent with a recent commentary on the current ROS debate (93), which suggested that differences in experimental conditions may help explain the incongruent conclusions regarding the ROS hypothesis reached by others based on the absence or minimal extent of such phenotypes (49)(50)(51). Our related recent work involving metabolic modeling of ROS production predicted and experimentally confirmed that even small increases in ROS levels can enhance antibiotic lethality (92).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Interesting recent work has illustrated that phenotypes such as cell death, mutagenesis, oxidative stress, and related activation of OxyR can all be reduced, depending on the method of culturing (101). These findings are consistent with a recent commentary on the current ROS debate (93), which suggested that differences in experimental conditions may help explain the incongruent conclusions regarding the ROS hypothesis reached by others based on the absence or minimal extent of such phenotypes (49)(50)(51). Our related recent work involving metabolic modeling of ROS production predicted and experimentally confirmed that even small increases in ROS levels can enhance antibiotic lethality (92).…”
Section: Discussionsupporting
confidence: 81%
“…These results, along with recent observations that kanamycin can damage DNA bases (26) and induce SOS response in strains with mutated 8-oxo-dG-processing genes (mutM, mutY, and mutT) (96), highlight a DNA-damaging component to aminoglycoside lethality, as is consistent with previous MutT results (25). More broadly, these findings suggest that suppressive alterations to proton motor force cannot wholly explain anaerobic protection against aminoglycoside lethality (49)(50)(51).…”
Section: Fig 5 Ros Contribute To the Lethality Elicited By Bactericsupporting
confidence: 87%
See 1 more Smart Citation
“…Oxidative damage was evidently essential for complete killing of cells. The initial results have been challenged (8)(9)(10), and very recently these challenges have been refuted (11). Evidently, oxidative stress contributes to the lethality of a variety of antimicrobial agents (12,13), including at least some antimicrobial peptides.…”
mentioning
confidence: 99%
“…coli, fabriquant ses centres Fe-S grâce à la machinerie SUF, présentait un degré de résistance aux aminoglycosides plus élevé que la même souche les fabriquant avec la machinerie ISC [47]. Les bases moléculaires de cette observation surprenante se trouvent dans les mécanismes associant transport et force proton motrice (PMF).…”
Section: Les Liens Inattendus Entre Fe-s Et Résistance Aux Antibiotiqunclassified